1990
DOI: 10.1128/jb.172.1.224-235.1990
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and antigenicity of the unique cell wall pimple of the Candida opaque phenotype

Abstract: Cells of Candida albicans WO-1 switch frequently and reversibly between two colony-forming phenotypes, white and opaque. In the white form, budding cells appear similar to those of most other strains of C. albicans, but in the opaque form, budding cells are larger, are bean shaped, and possess pimples on the wall. These pimples exhibit a unique and complex morphology. With scanning electron microscopy, a central pit can be discerned, and in many cases, a bleb can be observed emerging from the pimple center. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
116
0
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 21 publications
4
116
0
3
Order By: Relevance
“…On the other hand it has been reported that in the white-opaque high-frequency transition system (Slutsky et al, 1987), the switch between white and opaque phenotypes is accompanied by changes in the adhesion characteristics and surface properties of cells (Kennedy et al, 1988), and by changes in the antigenic composition of the cell surface Anderson et al, , 1990. Attempts to determine the surface components of C. albicans involved in adherence and antigenicity have revealed that cell wall mannoproteins fulfil this role (Casanova et al, 1989;Chaffin etal., 1988;Douglas, 1987;Sundstrom et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand it has been reported that in the white-opaque high-frequency transition system (Slutsky et al, 1987), the switch between white and opaque phenotypes is accompanied by changes in the adhesion characteristics and surface properties of cells (Kennedy et al, 1988), and by changes in the antigenic composition of the cell surface Anderson et al, , 1990. Attempts to determine the surface components of C. albicans involved in adherence and antigenicity have revealed that cell wall mannoproteins fulfil this role (Casanova et al, 1989;Chaffin etal., 1988;Douglas, 1987;Sundstrom et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences have been reported in the adhesion characteristics as well as cell surface properties (i.e. ultrastructure and antigenicity) between the socalled 'white' and 'opaque' cell phenotypes in the whiteopaque transition (Anderson et al, 1990;Kennedy et al, 1988), which is one of the three distinct switching systems (the WO-1 strain) described in C. albicans (Slutsky et al, 1987). These observations are of great interest, since adherence of fungal cells to the host tissues seems to play a transient but essential role in colonization.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the opaque phase, budding cells are elongate or bean-shaped, and roughly twice the volume of white cells (Slutsky et al, 1987). At the ultrastructural level, opaque cells differ from white cells in a number of characteristics, including the presence of a large vacuole filled with membranous or spaghetti-like material (Slutsky et al, 1987 ;Anderson et al, 1990), and opaque-specific cell-wall pimples Anderson et al, 1989Anderson et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…3. Opaque-phase cells of C. albicans, which possess pimples on their wall, seem to release small membranous vesicles that pass through the pimple canal and emerge from the pimples into the medium (Anderson et al, 1990).…”
mentioning
confidence: 99%